1982
DOI: 10.1007/bf01872259
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependence of catecholamine release from bovine adrenal medullary cells after exposure to intense electric fields

Abstract: By subjecting isolated adrenal medullary cells to intense electric fields of brief duration it is possible to gain access to the cell interior without impairing the ability of the cell to undergo exocytosis. After a single exposure to ~ field of 2kV/cm, ~=200 gsec, adrenal medullary cells behave as if their plasma membrane contains two pores of effective radius 2nm. At 37 ~ these 'equivalent pores' remain patent for up to lhr. The formation and stability of these 'pores' is not affected by the Ca content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
229
4
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(270 citation statements)
references
References 72 publications
35
229
4
2
Order By: Relevance
“…magnitude of the [Ca 2ϩ ] i elevations produced by mAChR activation is less than that produced by influx, the elevation produced by mAChR activation persists much longer and seems to affect a significantly greater portion of the chromaffin cell membrane. Based on estimates of the Ca 2ϩ dependence of exocytosis from bovine chromaffin cells (Knight and Baker, 1982;Augustine and Neher, 1992b) indicating that secretion can be initiated at [Ca 2ϩ ] i lower than 1 M, our results are consistent with previous reports implicating mAChRs in eliciting secretion in rat chromaffin cells (Wakade and Wakade, 1983;Malhotra et al, 1988). This contrasts with bovine chromaffin cells, in which release of Ca 2ϩ from intracellular stores by mAChR activation produces relatively weak elevations in [Ca 2ϩ ] i O'Sullivan et al, 1989) and is ineffective in producing secretion (Fisher et al, 1981;Kim and Westhead, 1989).…”
Section: Implications For Secretionsupporting
confidence: 91%
“…magnitude of the [Ca 2ϩ ] i elevations produced by mAChR activation is less than that produced by influx, the elevation produced by mAChR activation persists much longer and seems to affect a significantly greater portion of the chromaffin cell membrane. Based on estimates of the Ca 2ϩ dependence of exocytosis from bovine chromaffin cells (Knight and Baker, 1982;Augustine and Neher, 1992b) indicating that secretion can be initiated at [Ca 2ϩ ] i lower than 1 M, our results are consistent with previous reports implicating mAChRs in eliciting secretion in rat chromaffin cells (Wakade and Wakade, 1983;Malhotra et al, 1988). This contrasts with bovine chromaffin cells, in which release of Ca 2ϩ from intracellular stores by mAChR activation produces relatively weak elevations in [Ca 2ϩ ] i O'Sullivan et al, 1989) and is ineffective in producing secretion (Fisher et al, 1981;Kim and Westhead, 1989).…”
Section: Implications For Secretionsupporting
confidence: 91%
“…Yet Mg2+ in high amounts inhibited Ca2+-induced release in chromaffin cells permeabilized by high-voltage discharge (Knight and Baker, 1982). The experiments in this study were initially undertaken to look for inhibitory effects of Mg2+ in a-toxin-permeabilized PC 12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of regulated secretion has been studied extensively using permeabilized cell systems and patch-clamp techniques (Knight and Baker, 1982;Dunn and Holz, 1983;Vallar et al, 1987;Howell et al, 1987; for reviews see Gomperts, 1990;Almers, 1990;Burgoyne, 1990). These studies have identified calcium and GTP as two key components in this process; calcium and the nonhydrolyzable GTP analogue guanosine 5'-O-(3-thiotriphosphate) (GTPTS) 1 often act synergistically to trigger secretion from storage granules.…”
mentioning
confidence: 99%